Egg Production and Quality of Quails Fed Diets with Varying Levels of Methionine and Choline Chloride - . Khairani; . Sumiati; K. G. Wiryawan (Media Peternakan, 2016)
The aim of the present study was to determine the effect of choline chloride supplementation at 1500 ppm in diets containing various levels of methionine on egg production and egg quality in quails. A total of 180 birds, at 6 week-old quail were divided into 18 experimental units, and assigned to a 2 x 3 factorial design experiment with 3 replications (10 birds each) in each treatment. The birds were offered diets containing choline chloride at either 0 (A1) or 1500 ppm (A2), with three levels of methionine namely, low (0.19%, B1), standard (0.79%, B2) and, high (1.05%, B3). The feeding trial lasted for 8 weeks. Supplementation of choline chloride in low methionine diet significantly (P<0.05) increased egg production, egg mass, and egg weight as compared to those without choline chloride supplementation. Supplementation of choline chloride significantly (P<0.05) increased egg yolk weight but decreased albumen and egg shell weight as compared to those fed diets without choline chloride supplementation. It can be concluded that supplementation of choline chloride to a diet containing low methionine increased egg production, without affecting egg quality.